Dehydrogenation of Isobutane Over Nanoparticles of Pt/Sn Alloy on Pt/Sn/Na-Y Catalyst: The Effect of Tin Precursor on the Catalyst Behavior - Sedigheh Vaezifar; Hossein Faghihian; Mahdi Kamali (Iranian Journal of Chemistry & Chemical Engineering, 2009)
In this research Na-Y was synthesized by hydrothermal method and used as support for preparation of Sn/Pt/Na-Y catalysts using two different tin precursors, Bu3Sn(Cl) and SnCl2.2H2O, by sequential impregnation, in which the Pt  was deposited first and in the next step Sn was deposited. The catalysts were characterized by H2 chemisorption, transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), X-ray powder diffraction (XRD) and, thermogravimetrical analysis (TG) techniques. Elemental analysis of the catalysts was also carried out by X-ray fluorescence analysis (XRF). Dehydrogenation of isobutane was studied in a reactor under atmospheric pressure at 848 K. The conversion, selectivity and the yield of product and the efficiency of prepared catalysts were calculated. The aim of this work was to investigate effect of different Sn precursor and Pt dispersion on the performance of the prepared catalysts.